Independensi Mahkamah Konstitusi - Ahmad Fadlil Sumadi (Jurnal Konstitusi, 2016)
Amendment of the Constitution of the Republic of Indonesia Year 1945 (UUD 1945) define more clearly what is meant by judicial power and determine the perpetrators of judicial power. The judicial power as intended by the 1945 Constitution is the judicial power whereas the power needs to be guaranteed freedom (independency. Constitutional Court as one of the subjects of the judicial authorities in carrying out duties, functions, and authorities also uses the principle of independence and impartiality. The  existence  of  the  Constitutional  Court  as  a  subject  of  the judicial authorities which the authority determined in the 1945 Constitution, is necessary because amandment of 1945 Constitution have to led, among other things, the 1945 Constitution position as the supreme law of the state in which the authority of state agencies regulated.